Tunisia Agricultural Finance Study : Main Summary Report - World Bank (Washington, DC, 2014)
The Tunisia agricultural finance study was carried out in response to a request made in December 2009 by the Tunisian Ministry of Agriculture (MoA) for support for a study on the key constraints in agricultural finance. Technical and financial support was specifically requested for: (i) a comprehensive diagnostic analysis of the current mechanisms and problems of financing of the agricultural sector in Tunisia, including those by financial institutions and from budget resources, foreign direct investment, and insurance; (ii) a comparison of the Tunisian experience with successful experiences made in other comparable countries; and (iii) the formulation of concrete proposals. The diagnostic part was also requested to include the regulations pertaining to agricultural credit, other constraints impeding the development of agricultural finance, such as costs, profitability, professional organizations, extension services, research etc., and to look at the indebtedness of smallholders. It was also requested that the recommendations help to: (i) better define the objectives to be achieved in terms of financing of agriculture; (ii) increase the participation of the financial sector in financing agriculture; (iii) help identify need for support by different types of farmers; (iv) identify new instruments geared at qualitative and technological changes; (v) reduce the indebtedness of farmers; and (vi) help improve the subsidies for agricultural investment. There are two main written outputs of the Tunisia agricultural finance study. The experts working on the study have compiled a great deal of detailed background information diagnosing the current situation, describing practices in other countries, and providing recommendations on how to improve the situation in Tunisia. These details are provided in the accompanying full technical report, which should be of interest to technicians. The present report the main summary report provides a summary of the main findings and recommendations for policy makers.